2021
DOI: 10.1093/mnras/stab1225
|View full text |Cite
|
Sign up to set email alerts
|

An X-ray and radio study of the Hubble Frontier Field cluster Abell S1063

Abstract: We present results from Chandra X-ray observations and 325 MHz Giant Metrewave Radio Telescope (GMRT) observations of the massive and X-ray luminous cluster of galaxies Abell S1063. We report the detection of large-scale “excess brightness” in the residual Chandra X-ray surface brightness map, which extends at least 2.7 Mpc towards the north-east from the center of the cluster. We also present a high fidelity X-ray flux and temperature map using Chandra archival data of 122 ksec, which shows the disturbed morp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 70 publications
1
9
0
Order By: Relevance
“…A virial mass value of (2.17 ± 0.06) × 10 15 M was estimated by Sartoris et al (2020). Despite its regular shape, it appears to have recently undergone an off-axis merger, as inferred by Gómez et al (2012) and Rahaman et al (2021) from X-ray data, and by Mercurio et al (2021) from the dynamics of the members. Its high mass and redshift make it a very effective gravitational lens, which allows us to use the observed position of 55 spectroscopically confirmed multiple images from 20 background sources, distributed over a wide range of redshifts (z = 0.73−6.11; see Caminha et al 2016), to build an SL model.…”
Section: Abell S1063: Data and Analysismentioning
confidence: 97%
See 1 more Smart Citation
“…A virial mass value of (2.17 ± 0.06) × 10 15 M was estimated by Sartoris et al (2020). Despite its regular shape, it appears to have recently undergone an off-axis merger, as inferred by Gómez et al (2012) and Rahaman et al (2021) from X-ray data, and by Mercurio et al (2021) from the dynamics of the members. Its high mass and redshift make it a very effective gravitational lens, which allows us to use the observed position of 55 spectroscopically confirmed multiple images from 20 background sources, distributed over a wide range of redshifts (z = 0.73−6.11; see Caminha et al 2016), to build an SL model.…”
Section: Abell S1063: Data and Analysismentioning
confidence: 97%
“…The cluster is also a very bright X-ray source (L X ≈ 2.5 × 10 45 erg s −1 in the 0.1−2.4 keV band), due to the emission of the hot (T ≈ 12 keV) ICM (Rahaman et al 2021): it was identified as RXJ2248.7−4431 in the ROSAT All-Sky Survey (De Grandi et al 1999;Guzzo et al 1999).…”
Section: Abell S1063: Data and Analysismentioning
confidence: 99%
“…If the dynamical state of the cluster has been debated, recent work combining X-ray and radio observations indicates a disturbed state. AS 1063 is in an early stage of merging (see Rahaman et al 2021, and references therein).…”
Section: As 1063mentioning
confidence: 99%
“…ACB temperature map was produced by using a method described in Datta et al (2014); Schenck et al (2014); Hallman et al (2018);Alden et al (2019); Rahaman et al (2021). Spectra were extracted from the circular region centered on every pixel.…”
Section: Adaptive Circular Binning (Acb) Methodsmentioning
confidence: 99%